Treatment of Kimura disease with dupilumab: a case report and literature review - Yang, Wei; Wu, Ze; Niu, Jun (Frontiers in Immunology, 2026)
Kimura disease is a benign chronic inflammatory condition characterized by painless subcutaneous masses, peripheral blood eosinophilia, and increased serum immunoglobulin E levels. The pathogenesis of KD remains unclear, however, more and more evidence suggests that type 2 inflammation may play an important role in KD. We present a case of a 19-year-old male who complained of masses behind both ears for two months, ultimately diagnosed as KD. He showed a partial response to the initial systemic corticosteroid therapy. However, after tapering the dosage of corticosteroids, the patient’s symptoms did not improve, even with combined mycophenolate mofetil therapy. His symptoms worsened significantly after he discontinued treatment. Therefore, treatment with dupilumab was initiated at 600 mg, followed by 300 mg every two weeks. At week 20, the treatment was adjusted to 300 mg every four weeks for a duration of 32 weeks. The mass gradually reduced in size, accompanied by a progressive decrease in both the eosinophil count and IgE levels. These results show the significant efficacy of dupilumab in the management of KD.